EFFORTS TO DEVELOP RELIGIOUS AND MORAL VALUE ABILITY (IDENTIFY KNOW SALAH TIMES) USING A COMBINATION OF RHYMING METHOD AND MAKE A MATCH MODEL - Pratiwi, Diani Ayu; Aslamiah, Aslamiah; Sin, Ishak; Miliyawati, Dina (Journal of K6, Education and Management, 2018)
This is a classroom action research (CAR), which aims to identify the improvement of learning development outcome in developing the religious and moral value ability ??in recognizing Salah times by using a combination of rhyming method and make a match model in group A TK Nusa Indah Alalak Subdistrict, Barito Kuala Regency, involving 16 children consisting of 9 boys and 7 girls in the second semester of 2016/2017 school year. This research was conducted in two cycles, each cycle consists of two learning meetings. The research data source was obtained from the learning process using the combination of rhyming method and make a match model with the observation on teacher and children activities, the data in the form of evaluation was analyzed using percentage technique taken from the results of children worksheet (LKA). The learning implementation instruments as a support for this research were in the form of curriculum, syllabus, and RKH (daily activity plan). The data source in this research was group A children of TK NUSA INDAH, Alalak Subdistrict, Barito Kuala Regency. This research shows the development of religious and moral value ability ??(identifying Salah times) classically had obtained a score of ? ««« 93.75% and it was declared as successful in developing.